Removal of Chromium (VI) from Aqueous Solution Using Activated Carbon Derived from Modified Bambara Nut Shells (Vignasubterranea (L.) verdc.) - M. R. Abdullahi; M. I. Alkali (Journal of Applied Sciences and Environmental Management, 2023)
Adsorption of Cr (VI) ions from aqueous solution using activated carbon derived from Bambara nut shells (BBNSAC) was investigated using batch adsorption technique. The maximum removal of Cr (VI) ions onto BBNSAC corresponding to 68.00 mg/g was achieved at pH 2, adsorbent dosage 0.01 g and contact time of 60 minute. The Equilibrium data of adsorption revealed that the adsorption of Cr (VI) ions showed better fitting to Langmuir isotherm in comparison to Freundlich, Temkin and Dubinin-Radaushkevich isotherm models. The value of Langmuir monolayer coverage was 55.56 mg/g. However, the kinetics of adsorption was best described by pseudo second-order model with highest correlation coefficient, R2 value of 0.984. Thermodynamics parameters of adsorption revealed negative value of Gibb’s free energy (∆G) indicating a feasible and spontaneous adsorption process whereas the positive value of change in enthalpy (∆H) indicates that the adsorption process was endothermic in nature while the positive value of change in entropy (∆S) revealed that there is an increase in randomness at solid-solution interface during adsorption process.